Evaluación de adaptabilidad y descripción morfológica de 15 líneas de maíz (zea mays) amarillo tropical en el bajo mayo - Paredes Paredes, Semeías (2001)
The present work of “Evaluation of Adaptability and Description Morphology of 15 Lines of Com (Zea mays) Yellow Tropical in the First floor May", it was developed in lands of the Company Tobaccos of the Peru S. A. {TAPESA), located in the Km 10,5 of the highway marginal south, District of Juan Guerra. The experiment was carried out completely under the design of blocks Randomized, with 15 treatments (11 coming from INIA and 4 of the CIMMYT of Mexico) and 4 repetitions for treatment. Inside the results obtained in the experiment we can indicate that the Line PIMLE 77 coming from the INIA and the CML 287 that it comes from the CIMMYT of Mexico, presented bigger plant height, ear number and a potential of grain yield with 6 301,00 and 6,023,00 Kg /ha. As far the female flowering the precocious one turned out to be the Line PIMLE 56 with 5055 days and the late one was the Line PIMLE 118 with 57,91 days. For the masculine flowering the precocious one was the PIMLE 58 with 50,13 days and line late one was the one PIMLE 90 with 56,25 days, existing a period of two days among masculine and feminine flowering. The parameters like the color of the coleoptilo prevailed the one lived, in anthers the yellow, in stigma the Rosy one, in the central vein of the leaf and the leaves the green, the Line that had bigger sheet longitude to foliate was PIMLE 91 with 100,54 cm, the width and the area of the sheet to foliate the line PIMLE obtained 71 with 12,33 cm2 and 859,04, In the characteristics of the ear the ones PIMLE 11 PIMLE 117, they obtained 2 ears for plant, 16 arrays; the CML 287 35 grains for array, The ones CML 287 and CML 299 18 cm of longitude of the ear; the Line PIMLE 774.71 mm of ear diameter; the other ones characteristic in the experiment they are detailed in the table of results.